2015
DOI: 10.1088/1367-2630/17/1/013054
|View full text |Cite
|
Sign up to set email alerts
|

Limitations in artificial spin ice path selectivity: the challenges beyond topological control

Abstract: Magnetic charge is carried through nanowire networks by domain walls, and the micromagnetic structure of a domain wall provides an opportunity to manipulate its movement. We have shown previously that magnetic monopole defects exist in artificial spin ice (ASI) and result from two bar switching at a vertex. To create and manipulate monopole defects and indeed magnetic charge in general, path selectivity of the domain wall at a vertex is required. We have recently shown that in connected ASI structures, transve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…So far, global magnetic fields were typically considered to manipulate topological defects and thereby explore the path selectivity of evolving Dirac strings [8,13,29]. Our results offer a novel method to modify topological defects deterministically.…”
mentioning
confidence: 84%
“…So far, global magnetic fields were typically considered to manipulate topological defects and thereby explore the path selectivity of evolving Dirac strings [8,13,29]. Our results offer a novel method to modify topological defects deterministically.…”
mentioning
confidence: 84%
“…10 The field driven manipulation of pre-existing DWs in connected artificial spin ice systems is governed by the chirality and topological nature of the DW 11,12 and it's time-evolution during dynamic propagation. 13,14 These DWs typically originate at the edges of the sample as the reversal in the center of the array is constrained by the magnetization of the surrounding bars. 15 Therefore, the magnetization reversal in one bar triggers the reversal in neighbouring bars and leads to chains of reversal following Dirac strings in avalanche-like behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial spin ice structures have proven to be exemplary 35 systems in which to study frustration [5,6] and have been noted for their technological 36 potential as both a reconfigurable metamaterial and as a memory storage medium [7,8,37 9, 10,11,12]. Connected artificial spin ice in particular has been studied extensively in 38 the last decade [13,14,15,16,17,18,19,20,21,22,23,24,25]. Tanaka et al and 39 other workers, observed sharp features in the magnetoresistance of connected artificial 40 spin ice, and associated them with reversal events that maintain the ice rules of the 41 system [13,14,15].…”
mentioning
confidence: 99%